Analisis Struktur Modal Bank Syariah di Indonesia Menggunakan Non Performing Financing Sebagai Variabel Moderasi - Abadi, Ahmad; Widana, Gusti Oka (Jurnal Ilmiah Ekonomi Islam, 2024)
Capital structure is crucial in the financial management of Islamic banks, which operate under sharia principles. Since the practice of optimal capital structure can ensure the quality of bank operations, it is very important to analyze capital structure issues. This research aims to analyze the variables that determine the capital structure of Islamic bank with Non Performing Financing (NPF) as a moderating variable using the Trade Off Theory and Pecking Order Theory approaches. A quantitative method was used, analyzing panel data from the quarterly financial statement of 12 Indonesia Islamic banks form 2001-2003, using Eviews-12 software. The independent variables include bank size, profitability, Financing to Deposit Ratio (FDR), and asset growth, while the dependent variable is the Debt to Equity Ratio (DER). The study results imply that according to Trade Off Theory, Islamic bank in Indonesia balance the tax benefits of debt against bankruptcy costs. Related to Pecking Order Theory, Islamic banks in Indonesia are more likely to follow the order of funding preference, using internal funds first, then debt, and finally equity issuance. NPF as moderating variable, does not moderate all variables affecting capital structure.